ASPirin for Acute Pneumonia in the elderlY (ASPAPY): protocol of a multicentre randomised double-blind placebo-controlled trial - Sylvain Diamantis; Lionel Piroth; Gaetan Gavazzi; Isabelle Fournel; Caroline Laborde; Eléa Ksiazek; Amelie Cransac; Guillaume Deschasse; Alain Putot; Patrick Manckoundia; Marion Cortier; Mortada Adjim; et al. (BMJ Open)
Introduction Acute pneumonia (AP) remains a leading cause of death in the older population. Excess risk of death after AP is partly due to cardiovascular (CV) events. We aim to evaluate whether aspirin at a preventive dose (100 mg daily) introduced at the acute phase of AP reduces 90-day mortality.Methods and analysis The ASPirin for Acute Pneumonia in the elderlY study is a phase III multicentre randomised double-blind, placebo-controlled, superiority clinical trial, which will investigate the efficacy and safety of aspirin in older patients with AP hospitalised in a French university and non-university hospitals. Patients will be randomised in a 1:1 ratio between two groups receiving daily either 100 mg of aspirin or a placebo, within 84 hours following radiologically proven AP diagnosis for 90 days. This study aimed at assessing the efficacy of aspirin on all-cause mortality after AP at 90 days (D90) (primary objective), D30 and D120 after randomisation, CV mortality, major adverse CV events (MACE) (ie, myocardial infarction, stroke, heart failure, new atrial fibrillation and pulmonary embolism, CV death and sudden death) incidence, length of intensive care unit and hospital stay, unscheduled rehospitalisation, dependence, overall and MACE-free survival, as well as safety outcomes (bleeding incidence). The sample size, calculated considering a 90-day mortality of 25% and a reduction of 10% in the aspirin group, a two-sided alpha risk at 5% and power of 80%, is 500 patients to prove the superiority of aspirin over placebo. To account for screening failures and consent withdrawals, 600 patients (300 per arm) will be included.Ethics and dissemination This study has full approval from an independent Ethics Committee. Participants will sign a written informed consent ahead of participation. Findings will be published in peer-reviewed journals and conference presentations.Trial registration number EU CTIS: 2024-510811-32-00.